Web-based mind mapping learning media to increase understanding of economic policy materials - Meylinda Lukito Sari; Muhammad Abdul Ghofur (Harmoni Sosial: Jurnal Pendidikan IPS, 2020)
Against a background of students' lack of understanding of monetary and fiscal policy, the research conducted aims to develop learning media that is expected to be able to overcome these problems. Learning media developed using a mind mapping and web-based approach. This type of research used in this study is Research and Development with the 4D development model (Define, Design, Develop, Disseminate). Product trials conducted limited to 20 students by analyzing the results of the pre-test and post-test, which were calculated using the gain score and t-test. The test results show that web-based mind mapping learning media can improve students' understanding. Because by using this learning media, the active mental processes of each student become aroused, the material provided so that it is easy to remember. However, this web-based mind mapping learning media is still being tested on a limited basis, so it needs to be trialed in the broader audience to get more productive advice.